Force-velocity profiles of track cyclists differ between seated and non-seated positions - Dwyer, D. B.; Molaro, C.; Rouffet, D. M. (Sports Biomechanics, 2023)
The aim of the study was to compare the Force-Velocity profiles of track sprint cyclists obtained in seated and non-seated positions. Athletes were tested on a stationary cycle ergometer for the seated position and on a racing bike at the velodrome for the non-seated position. We modelled torque and power vs. cadence relationships and extracted maximal force (F0), optimal cadence (Copt), maximal power (Pmax), maximal cadence (C0) and Copt/C0 ratio. Torque/power production was larger in the non-seated position for cadences ranging from 20 to 120 rpm, while more torque and power were produced in the seated position at cadences above 160 rpm. The effective pedal force increased by 0.2 times bodyweight at 50 rpm, and the power production increased by 2.5 W. kg-1 at 90 rpm in the non-seated position. Copt (-14 ± 8 rpm, P < 0.05) and C0 (-55 ± 32 rpm, P < 0.05) were lowered, while Pmax (+1.7 ± 1.1 W. kg-1, P < 0.05) and Copt/C0 ratios (+0.07 ± 0.04, P < 0.05) were increased in the non-seated position when compared with the seated position. Our results show that adopting a non-seated position allows sprint cyclists to maximise torque/power production at lower cadences, while torque/power production was maximised at higher cadences when athletes adopted a seated position.